2007
DOI: 10.1126/science.1136466
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Determination of Air-Sea Momentum Exchange Under a Major Tropical Cyclone

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing the burden, to the Department of Defense, Executive Services and Communications Directora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
242
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(315 citation statements)
references
References 16 publications
39
242
2
Order By: Relevance
“…This trend in C d10 is a consequence of the regime of the limited saturation of the MABL dynamics, when the friction velocity at very high winds levels off. These features are in agreement with recent experimental data of Powell et al (2003), Powell (2006) and Jarosz et al (2007) acquired in hurricanes. The model predictions on the saturation of the friction velocity in the MABL are consistent with field data on saturation of the radar backscattering in hurricanes observed by Donnelly et al (1999).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This trend in C d10 is a consequence of the regime of the limited saturation of the MABL dynamics, when the friction velocity at very high winds levels off. These features are in agreement with recent experimental data of Powell et al (2003), Powell (2006) and Jarosz et al (2007) acquired in hurricanes. The model predictions on the saturation of the friction velocity in the MABL are consistent with field data on saturation of the radar backscattering in hurricanes observed by Donnelly et al (1999).…”
Section: Discussionsupporting
confidence: 82%
“…They found that the drag coefficient levels off and starts to decrease with a further increase in the wind speed above about 34 m s −1 . This finding was confirmed by Jarosz et al (2007) who found that the drag coefficient peaks at a wind speed near 32 m s −1 and then steadily decreases as the wind speed continues to rise. This is contrary to the traditional parametrizations that predict an increase of the drag coefficient with increasing wind speed.…”
Section: Introductionsupporting
confidence: 77%
“…(5). This approach follows Jarosz et al (2007), except in some momentum budget details such as bottom drag, which is necessary in shallow water but not here, and entrainment, which is included here but not in the shallow water case. Figure 7 shows the resulting stress estimates, converted to drag coefficients and plotted versus wind speed.…”
Section: B Momentum Balancementioning
confidence: 99%
“…The estimated storm's U h was also listed in Table 4. The scaled current speeds (U s ), which were estimated from C D of Jarosz et al (2007), are more similar to the observed U max (Table 4). Since the direct surface wind measurements are sparse under tropical cyclones, uncertainty exists in the estimate of maximum sustained wind speed (VMAX) and R max .…”
Section: Current Velocity Scale (U S )mentioning
confidence: 55%
“…Recent results indicated a saturation value of C D at the wind speed of 28-33 m s −1 (Donelan et al, 2004;Jarosz et al, 2007;Powel et al, 2003). Three semi-empirical formulas from Powel et al (2003), Black et al (2007), and Jarosz et al (2007) are used in this Table 4). The estimated storm's U h was also listed in Table 4.…”
Section: Current Velocity Scale (U S )mentioning
confidence: 99%